Aging-induced semaphorin 7a promotes TGF-β1-mediated cell plasticity and breast tumor metastases - Kelsey T. Kines; Heather R. Fairchild; Alan M. Elder; Lauren M. Cozzens; Zachary P. Strugar; Veronica M. Wessells; Alexandria R. Becks; Weston W. Porter; Virginia F. Borges; Traci R. Lyons (Cell Reports, 2025)
Summary: Breast cancer risk is transiently increased in postpartum women, and this risk is prolonged in women whose first childbirth occurs after age 30. We observe elevated semaphorin 7a (SEMA7A) in tumor tissues from patients with breast cancer aged 31–39 diagnosed <10 years after childbirth. In the aged normal murine mammary gland, transforming growth factor β+ (TGF-β+) cells have increased levels of surface SEAM7A compared to the young. TGF-β1 induces SEMA7A expression in non-transformed mammary epithelial and breast cancer cells via multiple mechanisms. In mouse mammary tumor models, we observe accelerated tumor growth and metastases, increased TGF-β+SEMA7A+ cells, and epithelial-to-mesenchymal plasticity in aged mice. SEMA7A knockout and heterozygous littermates reveal that these phenotypes depend on SEMA7A in the host. We further show SEMA7A’s pro-metastatic phenotype and abrogate it via a function-blocking antibody. Collectively, these results highlight the impact aging has on the mammary gland and the risk for breast cancer tumorigenesis.